Green synthesis of imidazole derivatives in a ternary deep eutectic solvent system - Fatemeh Mohammad; Najmedin Azizi; Zohreh Mirjafari; Javad Mokhtari (Scientific Reports)
Abstract Deep eutectic solvents (DESs) have gained recognition for their sustainable characteristics and demonstrated potential for various applications in chemical processes. Their biodegradability and recyclability make them an attractive alternative for sustainable chemistry. Herein, we investigated the application of novel ternary DES as a reaction medium and recyclable catalyst for one-pot, multicomponent synthesis of tri and tetra-substituted imidazole derivatives under mild conditions. A ternary DES composed of dimethyl urea, SnCl2, and HCl was prepared using a simple method from readily available starting materials. The structural and chemical composition of this ternary DES was characterized using FT-IR and EDX spectroscopy. The synthesis of various substituted imidazoles using the ternary DES has resulted in good to excellent yields, with high-purity products, which were achieved in a relatively short reaction time. Ternary DES exhibited remarkable properties as a cost-effective and environmentally friendly dual solvent and catalyst. The prepared DES exhibits excellent recyclability, with no noticeable decline in its catalytic performance even after five consecutive runs.